(untitled) (Diversity Research: Journal of Analysis and Trends, 2025)
This article discusses the significance of learning English in today’s world, where it has become a global language. It explores how English serves as a bridge for communication across nations, facilitates international business, enhances educational opportunities, and promotes cultural exchange. The article also highlights the role of English in technology, science, and diplomacy, explaining its status as a tool for global collaboration.